2015
DOI: 10.1155/2015/849573
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Interferon-Gamma Expression in CD8 T Cells

Abstract: Interferon- (IFN-) γ is an essential cytokine for immunity against intracellular pathogens and cancer. IFN-γ expression by CD4 T lymphocytes is observed only after T helper (Th) 1 differentiation and there are several studies about the molecular mechanisms that control Ifng expression in these cells. However, naïve CD8 T lymphocytes do not produce large amounts of IFN-γ, but after TCR stimulation there is a progressive acquisition of IFN-γ expression during differentiation into cytotoxic T lymphocytes (CTL) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 47 publications
1
46
0
1
Order By: Relevance
“…Co-administration of LEVA and GO modulated the rats' immune response towards a Th1/Th2 balance; therefore, maintaining the body's defensive mechanisms within normal ranges. IFN-γ is an essential cytokine for immunity against intracellular pathogens and cancer (23). Targeted disruptions of the IFN-γ gene or IFN-γ receptor 1 gene in mice render them highly susceptible to bacterial, protozoan and viral infections (24).…”
Section: A B C D E F G H I Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-administration of LEVA and GO modulated the rats' immune response towards a Th1/Th2 balance; therefore, maintaining the body's defensive mechanisms within normal ranges. IFN-γ is an essential cytokine for immunity against intracellular pathogens and cancer (23). Targeted disruptions of the IFN-γ gene or IFN-γ receptor 1 gene in mice render them highly susceptible to bacterial, protozoan and viral infections (24).…”
Section: A B C D E F G H I Discussionmentioning
confidence: 99%
“…Targeted disruptions of the IFN-γ gene or IFN-γ receptor 1 gene in mice render them highly susceptible to bacterial, protozoan and viral infections (24). The role of IFN-γ in CD8 T cell cellular immunity is to enhance the major histocompatibility complex class I antigen presentation pathway, which facilitates cytotoxic T cells to recognize infected cells (23). In the present study, the elevated levels of IFN-γ detected following LEVA treatment indicated its immunostimulatory effect towards induction and activation of Th1 cells, as reported in a previous Figure 3.…”
Section: A B C D E F G H I Discussionmentioning
confidence: 99%
“…Further evidences suggest that modifications of histones that lead to nucleosomal structural changes occur more often than in promoters regions [21]. For IFN-γ, modifications were detected at conserved noncoding sequences 1 (CNS1), CNS2, and Intron 3 [21,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…For IFN-γ, modifications were detected at conserved noncoding sequences 1 (CNS1), CNS2, and Intron 3 [21,22,23]. Thus, in addition to the promoter site, we also determined the H3K9, H3K14 acetylation, and H3K36me3 levels at the CNS1, CNS2, and Intron 3 sites within the ifng locus of rat spleen with prenatal dexamethasone or postnatal HF diet exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the proportion of Tc1 cells in LRG-47 −/− mice was significantly higher than that in WT mice. It suggested that the function of CD8 + T cell might be enhanced and IFN-γ produced by CD8 + T cells promoted the cytolytic activity (de Araujo-Souza et al 2015). Earlier studies suggested that in the chronic phase of Schistosoma mansoni infection, the increased CD8 + T cells contributed to downregulate granulomatous reaction of the existing and new-formed granulomas in the livers (Fidel and Boros 1990;Ragheb and Boros 1989).…”
Section: Discussionmentioning
confidence: 99%